Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts

Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition

Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling

Novel process for the synthesis of class I antiarrhythmic agent (+/-)-cibenzoline and its analogs - Gholap, Atul R.; Paul, Vincent; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Synthesis of (+/-)-cibenzoline and its analogs has been achieved by a simple sequence of reactions. The diaryl cyanoolefin intermediate 3 could be prepared by Knoevenagel condensation of benzophenone with ethylcyanoacetate to form the tetra-substituted olefin intermediate 2 followed by Krapcho deethoxycarbonylation or from beta-hydroxynitrile intermediate 2' followed by the elimination of hydroxyl group respectively. The 2,2-diphenylcyclopropanecarbonitrile 4 was synthesized from intermediate 3 by cyclopropanation, which was converted to (+/-)-2-(2,2-diphenylcyclopropyl)-2-imidazoline 5 by reaction with ethylenediamine in the presence of a catalytic amount of sulfur. Moreover, the obtained 2-imidazolines were smoothly oxidized to the corresponding imidazoles 6 in good to moderate yields.
Keywords: Benzophenone; cibenzoline; cyclopropanation; diaryl cyanoolefin